2019
DOI: 10.1016/j.cattod.2018.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Selective ring opening of decalin over bifunctional RuS2/zeolite catalysts

Abstract: The discovery of sulfur-resistant catalysts for selective ring opening (SRO) is an important challenge for refiners, considering the future legislation on cetane index of diesel fuels. In the present work, we studied the properties of RuS 2 supported on several zeolites in gas-phase decalin hydroconversion at high hydrogen pressure (5 MPa) in the presence of 0.8% H 2 S concentration. Catalytic bifunctionality was investigated by changing the Ru loading or support acidity. The addition of RuS 2 strongly improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Recently, Catherin et al found similar results in SRO of decalin; the addition of S to Ru catalysts supported on zeolite HY decreased coke formation and dehydrogenated products. [ 50 ] Therefore, some increase of the cracking reaction in the presence of sulphur could be due to the lower deposition of coke, as compared with the experiments in the absence of sulphur. Monteiro et al postulated that the main effect of the S is to modify the balance between the acid and metal activity, which alters the reactivity of the intermediate products and favours the cracking reactions.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Recently, Catherin et al found similar results in SRO of decalin; the addition of S to Ru catalysts supported on zeolite HY decreased coke formation and dehydrogenated products. [ 50 ] Therefore, some increase of the cracking reaction in the presence of sulphur could be due to the lower deposition of coke, as compared with the experiments in the absence of sulphur. Monteiro et al postulated that the main effect of the S is to modify the balance between the acid and metal activity, which alters the reactivity of the intermediate products and favours the cracking reactions.…”
Section: Resultsmentioning
confidence: 94%
“…Consequently, it could be concluded that the increase of metal content from 1 wt% to 2 wt% has little influence on decalin conversion as it was previously reported for RuS 2 /HY zeolite and Pt/Beta zeolite. [ 50,51 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supported Pd catalysts are commonly used for selective hydrogenation in the refining and petrochemical industry [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. When Pd catalysts are prepared via aqueous impregnation, the Pd precursor salts and corresponding precursor solutions with different pH values are important factors that could be used to control the interactions (e.g., electrostatic or ion-exchange interactions) between the Pd precursors and supporting materials such as alumina [ 12 , 13 , 14 ], silica [ 15 , 16 , 17 , 18 , 19 ], and activated carbon (AC) [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Supported Pd catalysts are commonly used for selective hydrogenation in the refining and petrochemical industry [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. When Pd catalysts are prepared via aqueous impregnation, the Pd precursor salts and corresponding precursor solutions with different pH values are important factors that could be used to control the interactions (e.g., electrostatic or ion-exchange interactions) between the Pd precursors and supporting materials such as alumina [ 12 , 13 , 14 ], silica [ 15 , 16 , 17 , 18 , 19 ], and activated carbon (AC) [ 20 , 21 ]. The microporous and mesoporous structures, surface properties, and functional groups of supporting materials also play important roles in controlling the dispersion and chemical state of Pd, hence it influences the performance of obtained Pd catalysts [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%